2017
DOI: 10.1080/09537104.2017.1353685
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiplatelet treatment in coronary artery disease patients: A necessary evil or an overzealous practice?

Abstract: In seeking to improve care in coronary artery disease patients, further platelet inhibition has been occasionally applied beyond that provided by aspirin and a P2Y receptor antagonist. This review aims to offer insights about the rationale, the efficacy and safety of combination antiplatelet therapy, involving three or more agents. Overall, the use of glycoprotein (GP) IIb/IIIa inhibitors did not significantly modify the treatment effect of different antiplatelet strategies, including double vs standard clopid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…ree GP IIb/IIa inhibitors are abciximab, tirofiban, and eptifibatide. Among them, abciximab is the most studied GP IIb/IIa inhibitor [37]. Basic research [27] found that GP IIb/IIIa inhibitors have the potential to treat MIRI.…”
Section: Modern Antiplatelet Therapy For Mirimentioning
confidence: 99%
“…ree GP IIb/IIa inhibitors are abciximab, tirofiban, and eptifibatide. Among them, abciximab is the most studied GP IIb/IIa inhibitor [37]. Basic research [27] found that GP IIb/IIIa inhibitors have the potential to treat MIRI.…”
Section: Modern Antiplatelet Therapy For Mirimentioning
confidence: 99%
“…The number needed to treat with a PPI in order to avoid a disabling bleed is over 300 in younger populations but this figure drops to around 25 in older adults. It is important to carefully consider the likely risk versus benefit of each antiplatelet and how many antiplatelets are required when selecting a treatment regimen for patients [41]. Platelet function tests may help to facilitate the choice of antiplatelet therapy [42,43].…”
Section: Reducing Upper Gi Bleeding By More Extensive Use Of Gastro Pmentioning
confidence: 99%
“…A 2015 systematic review of management of dental extractions in patients receiving warfarin determined that patients whose International Normalized Ratio (INR; a measure of warfarin's therapeutic index) was in therapeutic range (i.e., 3.0 or less) could continue their regular warfarin regimen prior to the procedure [42].Some of the recent drugs used are Cilostazol on top of aspirin and clopidogrel appears to be safe, although of questionable clinical benefit. In conclusion, combination antiplatelet therapy should be reserved only for selected cases and following thoughtful consideration of the associated risk/benefit ratio [45].…”
Section: Its Implications Inmentioning
confidence: 99%